2017
DOI: 10.1038/ncomms15415
|View full text |Cite
|
Sign up to set email alerts
|

A canonical neural mechanism for behavioral variability

Abstract: The ability to generate variable movements is essential for learning and adjusting complex behaviours. This variability has been linked to the temporal irregularity of neuronal activity in the central nervous system. However, how neuronal irregularity actually translates into behavioural variability is unclear. Here we combine modelling, electrophysiological and behavioural studies to address this issue. We demonstrate that a model circuit comprising topographically organized and strongly recurrent neural netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 54 publications
(92 reference statements)
1
35
0
Order By: Relevance
“…The fact that in Ref. [50] the correlations were independent of N and K [or were Oð1=KÞ when all neurons shared a common input] does not contradict our theory. In the architecture considered in Ref.…”
Section: Relation To Previous Workmentioning
confidence: 51%
See 3 more Smart Citations
“…The fact that in Ref. [50] the correlations were independent of N and K [or were Oð1=KÞ when all neurons shared a common input] does not contradict our theory. In the architecture considered in Ref.…”
Section: Relation To Previous Workmentioning
confidence: 51%
“…We recently studied the emergence of correlations in a network consisting of two strongly recurrent E − I subnetworks [50]. We showed that when one group of neurons in the first subnetwork projects to all excitatory neurons in the second subnetwork, the correlations in the second subnetwork are Oð1=KÞ.…”
Section: Relation To Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…If for example single DLM neurons contact multiple medium spiny neurons (MSNs) in Area X, similar to the way that thalamic neurons contact multiple MSNs in the mammalian striatum (Deschenes, Bourassa, Doan, & Parent, 1996;Kuramoto et al, 2009;McFarland & Haber, 2001;Parent & Parent, 2005), this would position them to correlate activity across the multiple neurons with which they form synapses. Modeling studies suggest correlations in activity enable neural networks to produce behavioral variability such as that generated by the AFP (Darshan, Wood, Peters, Leblois, & Hansel, 2017). One way to test for this function would be to reversibly and specifically inactivate thalamostriatal synapses in Area X and measure the effects on vocal variability.…”
Section: Functional Considerationsmentioning
confidence: 99%